Sohn-Rethel als Denker der Ökonomie - Oliver Schlaudt (Recherches Germaniques)
The article provides an outline of Alfred Sohn-Rethel’s philosophy of economics, which leads from the methodological criticism of neoclassical economics to the economic analysis of German fascism, from the criticism of management in modern business organization to considerations about future socialism. The connection with the author’s epistemological theses is also taken into account. Such a connection can be detected on the level of methodology, but also regarding the question of the role of science in production.